Revision of the genus Hyperomma Fauvel, 1878—part 1: New Zealand (Coleoptera: Staphylinidae: Paederinae) - Schomann, Andrea M.; Solodovnikov, Alexey (Zootaxa, 2014)
The New Zealand fauna of Hyperomma Fauvel, 1878, a rove beetle genus occurring only in Australia and New Zealand, is revised. Twenty-five Hyperomma species are reported from New Zealand, of which the following 17 new species are described here: Hyperomma montanum Schomann, n. sp., H. longicorne Schomann, n. sp., H. orientale Schomann, n. sp., H. bicoloripes Schomann, n. sp., H. johnnunni Schomann, n. sp., H. geminum Schomann, n. sp., H. geminoides Schomann, n. sp., H. variabile Schomann, n. sp., H. margali Schomann, n. sp., H. helenae Schomann, n. sp., H. julii Schomann, n. sp., H. inversicolor Schomann, n. sp., H. spatulae Schomann, n. sp., H. tridentatum Schomann, n. sp., H. boreale Schomann, n. sp., H. peninsulae Schomann, n. sp., and H. minutum Schomann, n. sp. Of the 10 Hyperomma species previously described from New Zealand by Broun, 8 are re-described, while two species are synonymized as follows: H. mandibulare Broun, 1893 = H. picipenne Broun, 1921, n. syn.; H. lobatum Broun, 1921 = H. discrepans Broun, 1921, n. syn. Lectotypes are designated for H. dispersum Broun, 1893 and H. duplicatum Broun, 1893. The New Zealand Hyperomma species are divided into 7 species groups, and identification keys to the species (one based on the aedeagi, one general) are provided. For each species pictures of the habitus and some details are given, the aedeagus is illustrated, and the known distribution is mapped. Finally, a generic key to the species of Paederinae occurring in New Zealand is provided.